Organizational Culture, Commitment and Teacher Performance: The Role of Job Satisfaction - Susi Widjajani; Khusnul Khotimah; Suyitno Suyitno; Dwi Jatmoko (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2022)
Teacher performance today is very much needed so that teachers can overcome and anticipate the challenges of changing times. An organization can make several efforts to improve the performance of its members, such as forming a strong organizational culture and commitment and creating job satisfaction for its members. This study aimed to examine the effect of organizational culture and commitment on teacher performance either directly or mediated by job satisfaction. The study respondents were private vocational high school teachers in Purworejo Regency in Indonesia using purposive sampling. The data was collected using a questionnaire, and then the data was processed using the Smart Partial Least Square method. The results indicate that organizational culture has a positive effect on teacher performance, while organizational commitment does not affect performance. Organizational culture and organizational commitment affect job satisfaction. Job satisfaction has an effect on performance. The conclusion from the results of this study is that organizational culture and organizational commitment, and the mediating role of job satisfaction are important factors for improving teacher performance. Keywords: Teacher performance, Organizational culture, Commitment, Job satisfaction